Pengaruh Motivasi dan Kompensasi Terhadap Kinerja Karyawan (Studi Kasus pada Karyawan PT. Tirta Investama Danone AQUA Semarang) - Muhammad Ilmal Faris; Sudharto Prawata Hadi (Universitas Diponegoro, 2019)
In the distribution department of PT. Tirta Investama Danone AQUA Semarang, there are several constraints in employee’s performance, including high number of late employee and not achieving the target quantity of goods distribute that makes down sales. This study aims to determine the influence of motivation and compensation on the employees’s performance at PT. Tirta Investama Danone AQUA Semarang. The type of research use explanatory research. The sample use 75 respondents in the distribution department PT. Tirta Investama Danone AQUA Semarang. The sampling technique use probability sampling. Data collection techniques use questionnaires, observations, and literature studies. Data analysis techniques use validity test, reliability test, correlation test, simple regression test, multiple linear regression test, t test, and f test with the help of IBM SPSS program (Statistical Product and Service Solutions) version 24.0. Based on the results of the analysis, the conclusion is the influence of motivation and compensation on employee’s performance at PT. Tirta Investama Danone AQUA Semarang through simple regression testing produces regression values of 0.404 and 0.619. The advice to the company is to give more rewards and penalties for employees who obey the rules and work according to the company's operational standards, evaluate the compensation given to employees each year, and increase employee’s compensation